Manipulation of Coherent Optical Propagation Based on Monolayer MoS2 Resonator - Huajun Chen (Photonic Sensors, 2019)
Abstract Atomically thin two-dimensional semiconductor nanomaterials have attained considerable attention currently. We here theoretically investigate the phenomena of slow and superluminal light based on the MoS2 resonator system driven by two-tone fields. Superluminal and ultraslow probe light without absorption can be obtained via manipulating the pump laser on- and off-resonant with the exciton frequency under different parameters regimes, respectively, of which the magnitude is larger than that in a carbon nanotube resonator. The bandwidth of the probe spectrum determined by the quality factor Q of MoS2 resonator is also presented. Furthermore, we also demonstrate the phenomenon of phonon induced transparency and show an optical transistor in the system. The all-optical device based on MoS2 resonator may indicate potential chip-scale applications in quantum information with the currently popular pump-probe technology.